Vivencias de familiares no processo de internação de crianças na unidade de terapia intensiva: uma revisão de literatura - COSTA, Gicelda Pimentel (2019)
The ICU is an environment of many technological advances, with modern equipment that becomes important in the treatment and reduction of mortality, both in pediatrics and neonatology. However, the ICU environment is still seen with prejudices and becomes an even more delicate experience when it comes to the hospitalization of a child, being surrounded by fear and anxiety by the mother and family. Therefore, the present study aimed to present the evidence in the literature about the experiences of relatives in the process of hospitalization of children in the intensive care unit, from 2008 to 2017. The method used is characterized as a review of the literature. The search was performed on the platform of the Virtual Health Library - VHL, in the Latin American and Caribbean Literature database on Health Sciences - LILACS, using the descriptors "family child" and "intensive care unit" and established as criterion of inclusion for the selection of the sample: complete articles with public availability, published in Portuguese in the period from 2008 to 2017, to attend the experiences of relatives in the process of hospitalization of children in the intensive care unit. The result of the collection totaled fourteen (14) articles, giving rise to three categories, being: changes of routines faced by relatives in the ICU environment; the look of nursing and the relationship with relatives; support and support to family members in the ICU. The aim of this study is to contribute to the construction of knowledge and reflection through evidence within the literature about the experiences of family members during hospitalization, such as feelings of anxiety and fear during hospitalization, opening the way to better care and well-being favoring the confrontation of the family member within the ICU. Descriptors: family child; intensive care unit.